login
Let b(0)=0; b(1)=1; b(n+2)=(e^g-1/e^g)*b(n+1)+b(n). a(n)=floor(b(n)).
4

%I #4 Oct 19 2017 03:14:27

%S 0,1,1,2,4,7,13,24,43,76,137,244,435,774,1379,2457,4377,7796,13886,

%T 24732,44050,78456,139736,248880,443274,789503,1406162,2504477,

%U 4460655,7944750,14150175,25202487,44887455,79947808,142392836,253611954

%N Let b(0)=0; b(1)=1; b(n+2)=(e^g-1/e^g)*b(n+1)+b(n). a(n)=floor(b(n)).

%C g is Euler's gamma, 0.5772156649...

%C a(n+1)/a(n) converges to e^g.

%Y Cf. A090039, A090426, A093607, A093608.

%K nonn

%O 0,4

%A _Gary W. Adamson_, Nov 30 2003

%E Edited by _Don Reble_, Nov 14 2005